IDENTIFIKASI GEJALA DAN PENYEBAB PENYAKIT BUAH JERUK IMPOR DIPENYIMPANAN DI KOTA PEKANBARU - Yetti Elfina; Muhammad Ali; Siti Maysaroh (Jurnal Sagu, 2012)
Citrus production in Riau have been in inadequate to meet the people's consumptionin terms ofboth quality and quantity. This presents an influx of imported fruits, including oranges in Riau. The entryof imported fruit can carry pathogens that can degrade the quality of these fruits. Research was conductedin the Laboratory of Plant Diseases of Agricultural Faculty of Riau University of from June to August2011. Purpose of this study was to identify the symptoms and causes disease in citrus fruit imports duringpost harvest in Pekanbaru. Research conducted using survey method with the determination of marketsamples are purposive sampling. Of the mind that a disease affecting citrus fruit imports in the cityPekanbaru in the supermarket is Anthracnose disease caused by Colletotrichum sp, Aspergillus rot causedby Aspergillus sp, Fusarium rot caused by Fusarium sp and Alternaria fruit rot caused by Alternaria sp.In traditional markets is a disease and rot Anthracnose disease Aspergillus.